SCALE‐UP OF SAFE & CIVIL SCHOOLS' MODEL FOR SCHOOL‐WIDE POSITIVE BEHAVIORAL INTERVENTIONS AND SUPPORTS. Issue 4 (29th February 2016) - Smolkowski, Keith; Strycker, Lisa; Ward, Bryce
Abstract : This study evaluated the scale‐up of a Safe & Civil Schools Foundations: Establishing Positive Discipline Policies positive behavioral interventions and supports initiative through 4 years of "real‐world" implementation in a large urban school district. The study extends results from a previous randomized controlled trial that established the effectiveness of the Safe & Civil Schools program in 32 elementary schools in the same district. This study emphasizes the application and evaluation of the program in regular district schools. Four‐year results indicate that elementary, middle, and high schools experienced moderate but steady improvements in (a) school discipline, (b) student safety policy and training, (c) staff perceptions of student behavior, and (d) student suspension and chronic tardiness rates. With few exceptions, improvements occurred after schools began Safe & Civil Schools Foundations training, and more years of training were associated with larger cumulative improvements in school and student outcomes. Given that similar effects were observed in schools with and without random assignment of training, and only after training began, we concluded that the improvements stem from Safe & Civil School's Foundations training.